COVID-19 and First Responder Social Workers: An Unexpected Mental Health Storm. Issue 2 (29th January 2022) - Davies, Holly; Cheung, Monit
Abstract: COVID-19 has disproportionally affected people living in poverty; new immigrants; and those living in healthcare settings (hospitals, clinics, and nursing homes), shelters, detention centers, and prisons. The pandemic has also significantly impacted social workers who face hidden mental health consequences. The resultant feelings and behaviors are similar to disaster-induced trauma, including excessive rumination, hypervigilance, exhaustion, and excessive crying as a result of the adrenaline-driven fight-or-flight response. This article aims to provide information for social workers to protect their own mental health while caring for their clients and raise awareness about social workers' needs in frontline duties. It summarizes five challenges for first responder social workers: (1) COVID-19 impacts on resource constraints, (2) employment insecurity, (3) disenfranchised guilt, (4) physical distancing and caution fatigue, and (5) managing self-care. The article offers recommendations to ameliorate distress and promote advocacy efforts for readjustment. As COVID-19 cases continue to rise, social workers who provide essential care in the field need self-assessment to better understand the impacts these challenges have on them as helpers. The article ends with recommendations to encourage social workers to apply the strengths-based approach to exemplify their professional values in times of pandemic distress.